Effects of Different Fluoride-containing Toothpastes on In Vitro Enamel Remineralization - KARGÜL, BETÜL (BEZMIALEM VAKIF UNIV, 2019)
Objective: Fluoride toothpaste is one of the most effective cariostatic product when used as a daily fluoride application. The purpose of this in vitro study was to evaluate the effect of a new fluoride-containing toothpaste on enamel surface microhardness (SMH) under a pH-cycling regimen. Methods: Thirty-five sound human enamel samples were randomly divided into five groups (A-E) each containing seven samples as A (fluoride-free control group), B (1000 ppm NaF), C [KNO3 (5%), 1450 ppm NaF], D (1450 ppm sodium monofluorophosphate), and E (1450 ppm NaF). After inducing caries-like lesions, each group was maintained daily for de- and remineralization cycle for seven days. During this cycle, samples were treated by the selected toothpaste for each group. Enamel mineral loss was assessed by SMH and lesion depth was analyzed by polarized light microscopy (PLM). Surface enamel microhardness was determined on the enamel blocks. SMH recovery (%SMHR) among treatments was analyzed by a two-way ANOVA. Results: The highest values of %SMHR were observed for the 1450 ppm NaF (group C). NaF toothpastes significantly increased the microhardness of the lesions (pc0.001) when compared to control groups. PLM data resealed a mineral precipitation hand on the surface layer of all samples but no difference was found between groups in terms of enamel remineralization layers (p>0.05). The results suggest that all toothpastes with similar sources/concentrations of fluoride, provide different levels of remineralization. Conclusion: It can be concluded that new NaF compounds in toothpaste result in a clearly marked remineralization of caries-like enamel lesions.
Keywords: pH cycle; toothpaste; remineralization; demineralization; PH-CYCLING MODELS; CALCIUM-PHOSPHATE; MICROHARDNESS; DENTIFRICES; EFFICACY; LESIONS